1995
DOI: 10.1002/ptr.2650090207
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effects of propolis extract on carbon tetrachloride‐induced liver injury in rats

Abstract: The effects of an ethanolic extract of Cuban red propolis were examined using the model of acute hepatotoxicity induced by carbon tetrachloride (CCL,) in rats. Propolis extract at doses of 5, 10 and 25 mg/kg i.p. decreased significantly the activity of alanine aminotransferase and the concentration of malondialdehyde in rat serum as well as the concentration of triglycerides in liver which were increased in CCI,-treated animals. An ethanol extract of red propolis also reduced liver damage induced by CCl., in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 19 publications
3
21
0
1
Order By: Relevance
“…The pharmacological properties of different propolis preparations have been reported as antihepatotoxic (Gonzales et al, 1995), anticarcinogenic (El-khawaga et al, 2003), antioxidative (Russo et al, 2002), neuroprotective (Nakajima et al, 2007), antiinflammatory (Borrelli et al, 2002), antimicrobial (Kujumgiev et al, 1999;Scheller et al, 1999;Koo et al, 2000;Marcucci et al, 2001;Abd El Hadi and Hegazi, 2002;Kartal et al, 2003;Al-Waili, 2005;Boyanova et al, 2005;Papova et al, 2005) and antiviral. Pharmacological activity against several viral infections has been demonstrated, e.g.…”
Section: Introductionmentioning
confidence: 98%
“…The pharmacological properties of different propolis preparations have been reported as antihepatotoxic (Gonzales et al, 1995), anticarcinogenic (El-khawaga et al, 2003), antioxidative (Russo et al, 2002), neuroprotective (Nakajima et al, 2007), antiinflammatory (Borrelli et al, 2002), antimicrobial (Kujumgiev et al, 1999;Scheller et al, 1999;Koo et al, 2000;Marcucci et al, 2001;Abd El Hadi and Hegazi, 2002;Kartal et al, 2003;Al-Waili, 2005;Boyanova et al, 2005;Papova et al, 2005) and antiviral. Pharmacological activity against several viral infections has been demonstrated, e.g.…”
Section: Introductionmentioning
confidence: 98%
“…In general propolis is a glue-like natural resinous substances that honey bees collected from a large variety of plant seedling and buds, which is used in folk medicine of at least 300 years b. c. (Ghisalberti, 1979). Propolis is a mixture of waxes, sugars and plant exudates and its chemical composition in diff erent samples includes more than 300 compounds, so its biological properties are diverse and its composition is directly related to that of the bud exudates collected by bees (Ghisalberti, 1979;Markham et al, 1996;Bankova et al, 2000;Banskota et al, 2001), in the animal nutrition the propolis has been added in grains or extract form into animals feed mixture as supplemental diet as well as antibiotic (Ghisalberti, 1979;Pepeljnjak et al, 1985;Velikova et al, 2000), antifungal (Dimov et al, 1991;Murad et al, 2002), antiviral (Amoros et al, 1994), local anesthetic (Paintz and Metzner, 1979), anti infl ammatory (Strehl et al, 1993;Miyataka et al, 1997), antioxidant (Sun et al, 2000;Isla et al, 2001), hepatoprotective (Gonzales et al, 1995), immune stimulating (Dimov et al, 1991), and cytostatic (Frenkel et al, 1993;Banskota et al, 2001). Prytzyk et al (2003) and Wang et al (2004) were found that the propolis has a positive eff ect on feed intake, body weight aslo they that found the propolis content flavonoid which led to improvement meat antioxidant.…”
Section: Introductionmentioning
confidence: 99%
“…Recent publications have reported that PP has a protective effect on chemical-induced liver injury. For example, pretreatment of rats with an ethanol extract of PP produced a hepatoprotective effect on CCl 4 -induced liver damage in histopathological and biochemical findings (Merino et al, 1996;Gonzalez et al, 1995). This also reduced liver damage induced by AA in mice, and markedly decreased the elevation of serum transaminase and hepatocellular fatty degeneration caused by chronic alcohol abuse in rats (Gonzalez et al, 1994;Lin et al, 1997).…”
Section: Discussionmentioning
confidence: 91%
“…Several biological activities such as anticancer, antioxidative, antiinflammatory and antibiotic activities have been reported for PP and its constituents (Burdock, 1998). Recently an ethanol extract of PP was shown to protect against liver injury induced by hepatotoxicants such as CCl 4 , alcohol and acetaminophen (Gonzalez et al, 1994;1995;Merino et al, 1996;Lin et al, 1997).…”
Section: Introductionmentioning
confidence: 97%